MAKNA METAFORA ANJING MENJULURKAN LIDAH DALAM SURAH AL-A’RAF AYAT 176: Pendekatan Psikologi Eksistensial - Amiyati Amiyati; Valisa Valisa; Paudji Astuti; Ahmad Mujahid (Sekolah Tinggi Ilmu Al-Qur'an Ar-Rahman, 2025)
The parable of the dog in Surah Al-A'raf verse 176 is a rich symbolization of the psychological state of human beings who experience dissatisfaction with life. This study seeks to uncover the layers of existential meaning of the metaphor through thematic approach and existential psychology. Using a qualitative-interdisciplinary methodology, this study combines thematic interpretation analysis (maudhu’i) with theory, especially the thought of Viktor Frankl and Carl Gustav Jung. The results show that the dog's behavior of